α-Amilase Inhibitory Activity of Fraction of Ethanolic Extract of Lebui Seed (Cajanus cajan (L.) Millsp.) Grown in West Nusa Tenggara - Dian Resti Setyaningrum; Rumiyati; Yekti Asih Purwestri; Satrijo Saloko; Agung Endro Nugroho; Yudi Pranoto; Sri Widyastuti (Journal of Food and Pharmaceutical Sciences, 2020)
Diabetes is a metabolic syndrome characterized by high blood sugar levels or hyperglycemia.Alpha-amylase inhibitors can be used as an antidiabetic that controls postprandial hyperglycemia.Alpha-amylase inhibitors are found in plants as protein and non-protein bioactive content such as in lebuiseed. The purpose of this study was to determine the activity of alpha-amylase inhibition of the fraction ofethanol extract of lebui seed. This research was carried out by extraction of lebui seed and then fractionatedlebui extract to obtain n-hexane fraction (HF), ethyl acetate fraction (EAF), and water fraction (WF). Thefractions then tested to alpha-amylase inhibition activity in vitro by measuring the reducing sugar using3.5-dinitrosalicylic (DNS) reagent. Furthermore, the identification of the bioactive content of each fraction wascarried out using thin layer chromatography. The results of alpha-amylase inhibition activity test showed thatall fractions had the ability to inhibit alpha-amylase. The IC50 value of the n-hexane fraction, ethyl acetatefraction, and water fraction were 173.05 mg/ml, 9.98 mg/ml, and 137.19 mg/ml, respectively. Ethyl acetatefraction has the smallest IC50 value compared to other fractions. Based on the identification of the bioactivecontent, bioactive content that is only found in the ethyl acetate fraction but not in other fractions are tannins.Therefore, the chemical content in lebui seed which acts as an alpha-amylase inhibitor might be tannins.